Unveiling novel biomarkers for platinum chemoresistance in ovarian cancer - Wang Caixia; Peng Changsheng; Xie Chuan (Open Medicine)
Primary chemoresistance to platinum-based treatment is observed in approximately 33% of individuals diagnosed with ovarian cancer; however, conventional clinical markers exhibit limited predictive value for chemoresistance. This study aimed to discover new genetic markers that can predict primary resistance to platinum-based chemotherapy. Through the analysis of three GEO datasets (GSE114206, GSE51373, and GSE63885) utilizing bioinformatics methodologies, we identified two specific genes, MFAP4 and EFEMP1. The findings revealed that the areas under the receiver operating characteristic curves for MFAP4 and EFEMP1 were 0.716 and 0.657 in the training cohort, and 0.629 and 0.746 in the testing cohort, respectively. In all cases or in cases treated with platin, high expression of MFAP4 and EFEMP1 was linked to shortened overall survival and progression-free survival. MFAP4 and EFEMP1 were positively correlated with epithelial–mesenchymal transition, TGF-β signaling, KRAS signaling, and so on. The high expression groups of MFAP4 and EFEMP1 exhibited elevated stromal, immune, and ESTIMATE scores. Finally, we constructed a regulatory network involving lncRNA–miRNA–mRNA interactions. In summary, MFAP4 and EFEMP1 have the potential to serve as predictive indicators for both response to platinum-based chemotherapy and survival rates, and might be regarded as innovative biomarkers and therapeutic targets for OC patients.